Effect of Trust between the Time Pressure and Complexity in Judging and Decision-Making in Auditing - Cleston Alexandre dos Santos; Paulo Roberto da Cunha (RAC: Revista de Administração Contemporânea, 2021)
Objective: the study aimed to assess the moderating effect of confidence in the joint influence of time pressure and complexity in judgment and decision-making (JDM) in auditing. The behavioral decision theory (BDT) was used from the perspective of the anchoring heuristic. Methods: as a method, the 2x2x2 experiment was used with a final sample of 126 independent auditors. For analysis, the t-test and multiple linear regressions were used. Results: the findings allow us to infer that factors such as trust, time pressure, and complexity, individually and jointly, influence JDM. The study showed that trust moderates the joint influence of time pressure and complexity on JDM. Time pressure and task complexity negatively influence JDM, but when including trust as a moderating factor, the effect of time pressure and complexity is mitigated, reducing the auditor’s difficulties and uncertainties in JDM. Conclusion: the study contributes to BDT, moving academic research toward understanding the interrelationships between personal, environmental, and task factors. It also contributes by presenting evidence that there is a need for considering and observing the effects generated by the factors altogether, in order to contribute to improving the quality of the audit.